Targeting iNOS to increase efficacy of immunotherapies. Issue 5 (4th May 2017) - Ekmekcioglu, Suhendan; Grimm, Elizabeth A.; Roszik, Jason
ABSTRACT: Inducible NO synthase (iNOS/NOS2) protein expression is a well-studied predictor of poor outcome in multiple cancers, and it has also been associated with inflammatory and immunosuppressive processes in the tumor microenvironment. Immunotherapies are becoming increasingly key components in cancer treatment, and iNOS is receiving more attention as a potential regulator of treatment resistance. As we have reported in pancreatic cancer, by modulation of effector T-cell activity, iNOS overexpression may allow the tumor to escape the immune response through creating a microenvironment which causes recalcitrance to immunotherapy. Based on studies describing its role in the immune environment of multiple cancers, strategies that include iNOS inhibitors as combination partners may enhance immunotherapy approaches. The expression and the function of iNOS both depend on the tumor type and microenvironment, as well as on the patient's treatment history. Thus, enhancing immunotherapies, including adoptive T-cell therapies and checkpoint blockade, will require tailored cancer-specific approaches and additional levels of microenvironment regulation.